2003
DOI: 10.2302/kjm.52.236
|View full text |Cite
|
Sign up to set email alerts
|

Roots of Empathy: responsive parenting, caring societies

Abstract: Abstract. What is common in aggression and in abusive/neglectful parenting is low levels of empathy. Fostering empathy-the ability to identify with another person's feelings-can serve as an antidote to aggression and is crucial to good parenting. Poor parenting and aggression cut across all socio economic levels of the community and, as such, empathy needs to be fostered in all children. During the period of rapid brain development, adversity has a devastating impact on thebaby's developing brain. Repeated exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 3 publications
0
24
0
6
Order By: Relevance
“…[104][105][106] Health-care providers can also advocate for schools and school-based health clinics to adopt evidence-based, effective "Safe Date" programs.…”
Section: Controversy Over Ipv "Screening" and Rationale For Addressinmentioning
confidence: 99%
“…[104][105][106] Health-care providers can also advocate for schools and school-based health clinics to adopt evidence-based, effective "Safe Date" programs.…”
Section: Controversy Over Ipv "Screening" and Rationale For Addressinmentioning
confidence: 99%
“…Além disso, o desenvolvimento dos circuitos neuronais depende da estimulação ambiental, ou seja, das experiências vividas pelo indivíduo 2 . Experiências no começo da vida, combinadas com fatores genéticos, exercem importante influência em padrões de comportamentos apresentados na vida adulta 3 .…”
Section: Introductionunclassified
“…The program is designed for elementary school classrooms where a parent and an infant from the neighborhood visit the classroom on a monthly basis. A Roots of Empathy instructor coaches the students to observe the interactions between the infant and the parent in order to better understand the attachment that forms between the two and to recognize the empathetic responses and feeling between the two (Gordon, 2003). The children record the infant' s development over 27 lessons throughout the school year and learn to recognize the baby' s cues and temperament while learning to recognize feelings in others.…”
Section: Social-emotional Learningmentioning
confidence: 99%
“…shown that children learn to take the perspective of others and become less likely to bully and exclude others while building skills in democracy and gaining a sense of justice in the classroom (Gordon, 2003). Children demonstrate their learning through meaningful reflection, often through artwork which displays their interpretations of why the infant cries at certain times, for example.…”
Section: Social-emotional Learningmentioning
confidence: 99%
See 1 more Smart Citation